A cross-sectional study of determinants and impact of breastfeeding and complementary feeding practices on nutritional status and common illnesses among infants in urban slum - Masare, Monika S.; Soyam, Gajanan; Hiwarkar, P. A. (International Journal of Research in Medical Sciences, 2017)
Background: The present research was carried out with an objective to study various breastfeeding and complementary feeding practices its effect on nutritional status of children and association with common illness like diarrhea and ARI. Methods: This cross sectional observational study was conducted on infant registered in under five-clinic at an urban health center in urban slum. A semi structured questionnaire was used to study the current breast feeding and infant feeding practices among mothers of the study subjects. The analysis was done using Microsoft Excel. Results: There was universal breastfeeding with almost all children having ever been breastfed. Exclusive breastfeeding for the first six months was not practiced as only about 37.72% of infants were exclusively breastfed for six months. Factors associated with sub-optimal infant and young child feeding practices in these settings include mother’s education level, lack of knowledge of proper feeding practices, lower socioeconomic status, and frequent illness. Noncompliance with proper exclusive breast-feeding practices was associated with more chances of having diarrhoea and acute respiratory illness among infants. Conclusions: The study indicates poor adherence to WHO recommendations for breastfeeding and infant feeding practices leading to more chances of falling ill with common illnesses.